Mobil slakt av nötkreatur : konsekvenser för djuren, djurhållarna, slakteriföretaget och konsumenterna - Mattsson Lindgren, Janina (SLU/Dept. of Animal Environment and Health (until 231231), 2017)
More than 420,000 cattle are slaughtered in Sweden yearly and the vast majority of cattle are transported from the farm to the slaughter plant. Since many slaughterhouses are shutting down, the animals are exposed to longer transports, which may result in additional stress. By instead taking the abattoir to the farm, it may be possible to improve animal welfare and meat quality. Since the beginning of 2015 the Swedish company Hälsingestintan AB is running the first European mobile slaughterhouse for large cattle. The aim of this thesis is to illustrate how mobile slaughter of cattle affects animal welfare in comparison with conventional slaughter. By reviewing available scientific literature on the subject, consequences for the animals, the farmers, the slaughter company and consumers will be discussed. Complementary interviews have been made as well as novice on-sight observations. Meat quality has several dimensions that affect both consumers and producers. Stress is known to affect meat quality since high physical or psychological efforts will deplete the energy reserves in the muscles, which makes the pH in the animal rise. When this happens the meat properties can change dramatically. It can impact on texture, color and taste and in a worst-case scenario the meat is so affected that it cannot be sold, which is a great loss for the producers. The ethical aspect of buying meat is also an important matter for many consumers today, with increasing concerns about animal welfare. Much research indicates that mobile slaughter increases animal welfare. Yet, mobile slaughterhouses have potential issues. Stunning and bleeding is said to be more problematic and the production capacity is significantly lower than at a stationary abattoir. It is also discussed whether carcasses are cooled down fast enough at the mobile slaughterhouse and the limited access to fresh water is also a possible shortcoming. These potential issues can affect food hygiene and safety, which could be a disadvantage for both consumers and slaughter companies. Mobile slaughter companies also seem to have substantial challenges when it comes to profitability. Consumers might perceive a better meat quality from mobile slaughtered meat, although at a higher price.